การจัดการเรียนรู้แบบใช้บริบทเป็นฐานร่วมกับการใช้ข่าวเป็นสื่อ เรื่อง สภาพสมดุล เพื่อพัฒนาการรู้เรื่องวิทยาศาสตร์ของนักเรียนชั้นมัธยมศึกษาปีที่ 4 - สุขยิ่ง ศุภกร; บงกชเพชร ธิติยา; ดีแจ้ง นุชจิรา (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2017)
บทคัดย่อ การวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาวิธีการจัดการเรียนรู้แบบใช้บริบทเป็นฐานร่วมกับการใช้ข่าวเป็นสื่อในการพัฒนาการรู้เรื่องวิทยาศาสตร์เรื่อง สภาพสมดุล รูปแบบการวิจัยนี้เป็นการวิจัยปฏิบัติการในชั้นเรียนกลุ่มเป้าหมายนักเรียนชั้นมัธยมศึกษาปีที่ 4จำนวน 28 คนซึ่งได้จากการเลือกแบบเจาะจง โดยเครื่องมือที่ใช้ในการวิจัยได้แก่ แผนการจัดการเรียนรู้ทั้งหมดจำนวน 3 แผน แบบสังเกตพฤติกรรมการจัดการเรียนรู้ ใบงานและโปสเตอร์ของนักเรียน และแบบวัดการรู้เรื่องวิทยาศาสตร์ โดยทำการวิเคราะห์ข้อมูลเชิงเนื้อหาและการวิเคราะห์ข้อมูลเชิงปริมาณ ผลการวิจัยพบว่าวิธีการจัดการเรียนรู้แบบใช้บริบทเป็นฐานร่วมกับการใช้ข่าวเป็นสื่อควรมีลักษณะดังนี้ ครูใช้ข่าวเข้าสู่บทเรียนโดยนักเรียนร่วมกันระบุปัญหาและวิเคราะห์ปัญหาสู่การตั้งคำถามการหาความรู้และออกแบบการทดลองที่เหมาะสมนำไปสู่การทำการทดลองหาคำตอบจากนั้นนักเรียนนำเสนอผลการทดลองและความรู้ที่ค้นพบเชื่อมโยงกับปัญหา ครูนำข่าวอื่นที่มีแนวคิดเดียวกันมากระตุ้นให้นักเรียนได้ประยุกต์ใช้ความรู้สู่สังคมซึ่งส่งเสริมการพัฒนาการรู้เรื่องวิทยาศาสตร์ ส่วนผลการพัฒนาการรู้เรื่องวิทยาศาสตร์พบว่า นักเรียนแสดงสมรรถนะการอธิบายปรากฏการณ์ในเชิงวิทยาศาสตร์ได้สูงที่สุดร้อยละ 71.95 รองลงมาคือ สมรรถนะการแปลความหมายข้อมูลและประจักษ์พยานในเชิงวิทยาศาสตร์ร้อยละ 67.79 และสมรรถนะการประเมินและออกแบบการทดลองในเชิงวิทยาศาสตร์ร้อยละ 44.05 ตามลำดับ คำสำคัญ : การรู้เรื่องวิทยาศาสตร์, การจัดการเรียนรู้ใช้บริบทเป็นฐานร่วมกับการใช้ข่าวเป็นสื่อ, สภาพสมดุล ABSTRACT The purposes of this research were to find out about the effective ways of using context-based learning with news as media to enhance students’ scientific literacy and to develop scientific literacy through context-based learning with news as media in equilibrium topic for 10th grade students. This research was classroom action research model. The participants were 28 grade 10th students. The research tools comprised of the three learning plan of context-based learning with news as media approach, a classroom behavior observation form, the students’ work sheets and poster, and the scientific literacy test. The data was analysis by using content analysis and quantitative data analysis.For the results of the study, the proper learning managements of context-based learning with news as media approach are described as follows: teacher brings the news into the classroom using questions that encourage students to identify issues and analyze the problems within the news. Then students take questions that can be scientifically validated. They learn and design experiments that leading to experiment to find the answers. Then, they present experiment results and discovered knowledge linked to the problem. Finally, teacher brings other similar news with the same conceptual content to encourage students to apply knowledge in society, which promotes the development of scientific literacy.The results of the research illustrated that the most scientific competencies were developed that explain phenomena scientifically (71.95 percent). Then the second scientific competencies was Interpret data and evidence scientifically (67.79 percent) and the last one was evaluate and design scientific enquiry (44.05 percent). Keywords : scientific literacy, context-based learning with using the news media, equilibrium